Perspectives towards child abuse and neglect among dental practitioners in Belagavi city: A cross-sectional study - T V Soumya Mohanan; Roopali Manohar Sankeshwari; Anil V Ankola (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Child abuse (CA) is prevalent in every segment of society and is witnessed in all social, ethnic, religious, and professional strata. In this situation, dentists are in an ideal position to help detect signs of CA and should be able to recognize those signs. AIM: To assess the perspectives toward CA and neglect among dental practitioners of Belagavi city. MATERIALS AND METHODS: A cross-sectional survey was conducted among 102 dental practitioners. The data were collected by self-administered structured questionnaire. Data were analyzed using descriptive analyses for responses to each question, and Chi-square test was applied to test the association. RESULTS: 59.8% had learned the topic of CA and neglect as a student. Overall, 16 participants have recognized suspicious case of CA and neglect in their dental office. Only 34.3% had knowledge regarding the findings pointing to CA and neglect, and 96% had reported that there are barriers regarding reporting the same. 93% are of opinion that the topic is of utmost importance and more training is required in this aspect. CONCLUSION: Training and continuing dental education programs should be tailored to the specific needs of all professionals to diagnose, report, and prevent CA.